2015
DOI: 10.1002/ceat.201400578
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Sparger Type and Added Alcohol on the Gas Holdup of an External‐Loop Airlift Reactor

Abstract: The influences of alcohol adding and three different gas spargers (single orifice, perforated plate, and sinter plate) on the gas holdup in an external-loop airlift reactor were studied. The experimental results show that the gas holdup can be increased by mutual influence of both the alcohol adding and the sparger type. The presence of small amounts of normal aliphatic alcohols caused an increase of the gas holdup compared to the air-water system, due to their coalescence-inhibiting nature. The sinter plate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 44 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…The transition between regimes was identified by the change of the slope of the gas holdup vs. the gas velocity curves. A more detailed analysis of hydrodynamic regimes and transition superficial gas velocities was described in our earlier study (Kojić et al, 2015). The transition points in the ELAMR appeared at a slightly lower U G compared to the ELAR.…”
Section: Hydrodynamic Regimesmentioning
confidence: 83%
“…The transition between regimes was identified by the change of the slope of the gas holdup vs. the gas velocity curves. A more detailed analysis of hydrodynamic regimes and transition superficial gas velocities was described in our earlier study (Kojić et al, 2015). The transition points in the ELAMR appeared at a slightly lower U G compared to the ELAR.…”
Section: Hydrodynamic Regimesmentioning
confidence: 83%
“…Also, it was visually observed that with the raise in methanol concentration the bubbles broke up into many smaller bubbles. The similar trend for the increase in gas holdup with a decrease in surface tension was observed in previous studies , . The results are also in accordance with the study of Besagni et al.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier, researchers , investigated the effect of surfactant concentration on gas‐phase holdup in airlift reactors by considering different concentrations of aliphatic alcohols. They observed that with an increase in the concentrations of various alcohol solutions/number of carbon atoms and superficial gas velocity, the gas‐phase holdup became higher.…”
Section: Introductionmentioning
confidence: 99%
“…This can be explained by changes in the surface tension gradient that causes the different coalescence suppression strength of specific alcohol. Therefore, alcohols with lower C-atoms show lower surface tension gradients and produce lower gas holdup values [44]. In the same manner, surface tension decrease with the augment of alcohol concentration, while surface tension gradient rises and consequently leads to increase in the gas holdup of the ELAR.…”
Section: Figurementioning
confidence: 86%
“…The results showed that the increase of the surface tension gradient, as a consequence of alcohol addition, has a strong impact on hydrodynamics and mass transfer characteristics of airlift reactor. The increase of surface tension gradient corresponds to the increase of the number of carbon atoms in alcohol molecule [42][43][44]. Alcohol addition has a remarkable effect on the gas holdup.…”
Section: Figurementioning
confidence: 99%